On E(11) of M-theory: 1. Hidden symmetries of maximal supergravities and LEGO of Dynkin diagrams - Nurmagambetov, A.J. (Вопросы атомной науки и техники, 2007)
We review a graphical way of classifying hidden symmetry algebras and groups of D=11, 10 maximal supergravities in terms of Dynkin diagrams, the shapes of which are determined by the bosonic field content of supergravities supermultiplets. The approach we follow is tightly related to the West’s conjecture on a hidden symmetry of M-theory, and we discuss benefits of the approach in compare to other ways of searching for hidden symmetries of String Theory. Подано огляд графічного методу класифікації алгебр і груп прихованих симетрій D=11, 10 максимальних супергравітацій в термінах діаграм Динкіна, форма яких визначається складом бозоних полів супергравітаційного супермультиплету. Запропонований підхід тісно пов'язаний з гіпотезою Веста про приховану симетрію М-теорії, і обговорюються переваги даного підходу в порівнянні з іншими способами знаходження прихованих симетрій Теорії Струн. Представлен обзор графического метода классификации алгебр и групп скрытых симметрий D=11, 10 максимальных супергравитаций в терминах диаграмм Дынкина, форма которых определяется составом бозонных полей супергравитационного супермультиплета. Предлагаемый подход тесно связан с гипотезой Веста о скрытой симметрии М-теории, и обсуждаются преимущества данного подхода по сравнению с другими способами нахождения скрытых симметрий теории Струн.